AUTOMATED METERING SYSTEM FOR CONTROL OF THE SPATIAL-ANGULAR DEVIATIONS - G. A. Zvetkov (Pribory i Metody Izmerenij, 2015)
Automatic metering system using devices and instruments for inertial navigation has been elaborated. The system allows more accurate measurement of angular deviation of installation sites for scientific equipment. Enhanced functionality is achieved by additional measuring of the azimuth angle error.